(untitled) (Perner’s Contacts, 2011)
The problem which deals with pricing in public passenger transport is discussed in this article. This problem is a reset of Regulation (EC) No 1370/2007 and its application to practise. Because of unpreparedness authority, Slovak agreements of 2011 don’t accept the principle of neutrality and the reasonable profit is specified as a percentage of costs. The article states manners of remuneration operators in Europe.